Peran Dukungan Orang Tua dalam Meningkatkan Kemampuan Belajar Siswa Kelas 1 SDIT Tahfidzul Qur’an Sawahlunto - Salsabila Salsabila; Rosi Oktavia; Safrizal Safrizal; Mega Adyna Movitaria; Susi Ratna Sari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study investigates the role of parental support in improving the learning abilities of elementary school students, with a particular focus on first-grade students at Tahfidzul Qur'an Elementary School. The research was motivated by the growing recognition that parental involvement is a key factor influencing children's academic development and learning success during the early years of education. A qualitative approach with a case study design was employed to gain an in-depth understanding of how parental support contributes to students' learning experiences. Data were collected through classroom observations, semi-structured interviews with teachers and parents, and documentation of relevant school records. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing and verification. The findings reveal that parental support positively influences students' learning abilities by increasing motivation, fostering positive learning habits, encouraging active participation in school activities, and strengthening communication between home and school. Students whose parents consistently provided emotional, motivational, and academic support demonstrated better learning outcomes and greater engagement in classroom activities. The study concludes that parental support plays a crucial role in enhancing elementary students' learning abilities and emphasizes the importance of strong collaboration between parents and schools to create an effective and supportive learning environment.